Maternal and foetal outcome of acute kidney injury in pregnancy single centre experience from North India - Saxena, Sumanyu; Beg, Mujahid; Aslam, M.; Akhtar, Nishat; Kumar, Prakhar (International Journal of Research in Medical Sciences, 2023)
Background: The diagnosis and treatment of acute kidney injury in pregnancy is a challenge to the physician as various pathophysiological changes take place during pregnancy, variability of symptoms and occasionally overlapping laboratory and clinical features. The occurrences of feto-maternal mortality associated with it decreased in developing nations due to increased prenatal and postnatal care and improved medical facilities. This study was undertaken to provide insight into feto-maternal outcome in patients presenting with acute kidney injury (AKI) during pregnancy. Methods: This was an open label prospective hospital-based cohort study comprising patients admitted in obstetrics and nephrology wards, presenting with AKI and no known chronic illnesses prior to pregnancy. Following criteria were used to diagnose AKI during pregnancy: (a) Elevation of S. creatinine ≥ 1 mg/dl; (b) Oligo-anuria for ≥ 12 hours and (c) Need for RRT. 50 such cases were enrolled in the study. Results: Out of all patients enrolled, majority (60%) had improved renal function, 16% expired, and 24% had no recovery in renal function. Out of all patients taken for haemodialysis, 20% of patients had improved renal function, 20% expired and 60% had no recovery in renal function. Mean S. creatinine on 3 months follow-up in conservative group found-1.67±1.31 mg/dl. 60% pregnancies resulted in the birth of a live baby and rest resulted in foetal loss. Conclusions: In our study, it was found that acute kidney injury in pregnancy results in significant feto-maternal mortality and morbidity. Those patients, who had significant renal derangement and concomitant complications, had poorer outcome.